Optimalisasi Penyaluran Zakat, Infak, Sedekah (ZIS) Baznas Kota Pasuruan Terhadap Tingkat Kesejahteraan Mustahik - Mukhamad Ikhlas Darmawan; Nihayatu Aslamatis Solekah (Jurnal Ilmiah Ekonomi Islam, 2022)
Zakat has a very important role in efforts to minimize the level of poverty or economic development. This is in order to achieve prosperity in which distribution optimization is still being questioned in Pasuruan City. This qualitative study aims to obtain informations about distribution optimization of Zakat, Infaq, Shadaqah (ZIS) of National Amil Zakat Agency (Baznas) to the welfare level of mustahik Zakat, Infaq, Shadaqah (ZIS) in Pasuruan City. This study involved 20 mustahik (13 mustahik for living expenses, 4 mustahik for working capital, 2 mustahik for work equipment, 1 mustahik for goats) who were positioned as research subjects. Research data were collected using integrated primary data from interviews, observations, and documentation. The data collected were analyzed using triangulation techniques sourced from data reduction, data presentation, conclusion drawing, and verification. As a result, the distribution optimization of Zakat, Infaq, Shadaqah (ZIS) of National Amil Zakat Agency (Baznas) can be distributed properly and on target. It also has an impact on the welfare level of mustahik. It is optimalized through the Program of Pasuruan Care, Smart Pasuruan City, and Prosperous Pasuruan City. There is one aid that has not yielded results, namely the assistance of goats where the livestock do not have offspring. By following up on the findings of this research, the performance of programs should be optimized, especially, in terms of increasing zakat assistance which can help increase mustahik's income because on many mustahik can only earn income from the type of business they run